Preparation of Graphene Nanosilver Composites for 3D Printing Technology - Xiujuan Liang; Haixu Ji (Advances in Materials Science and Engineering)
At present, graphene in two-dimensional carbon nanomaterials is a material with excellent properties. Its preparation technology and application prospects are very wide. The most common one is the chemical redox method, which can make graphite into graphite oxide dispersed in water. Graphene oxide obtained by the Hummers method has a wrinkled structure. In order to broaden the application field of graphene and give full play to its excellent properties, the current research on graphene mainly focuses on the preparation and application of functional composite materials as a matrix material or reinforcement material. Due to its special two-dimensional structure, it has a large specific surface area, good biocompatibility, and stable physical and chemical properties, making it an excellent nanoparticle carrier. The graphene-supported silver nanoparticles can effectively prevent the aggregation and stacking between particles, improve the electrochemical performance of the composite material, and expand its application range. In this article, the assisted preparation of graphene nanosilver composites by 3D printing technology (three-dimensional printing) was studied. 3D printing technology is a rapid prototyping technology that emerged in the 1980s. 3D printing technology is based on discrete stacking and realizes rapid processing of models by directly outputting data from the printing device. In this article, a new type of graphene oxide (GO) was prepared by the modified Hummers method. In the case of NaOH aqueous solution as a catalyst, silver nitrate and GO were used as precursors, and XRD, infrared spectrum, Raman spectrum, and other methods were used. The crystal structure and morphology of Ag/rGO under different conditions were studied, thus revealing the growth of silver particles and the changes of oxidized functional groups under different conditions. It was found that the intensity of the two peaks in the GNs-Ag-2 Raman spectral curve was seven times that of the GNs peak.